Necrotizing histiocytic lymphadenitis due to three cases applying with painful cervical lymphadenopathy - Yardimci, Bulent (Asian Journal of Medical Sciences, 2021)
Necrotizing Histiocytic Lymphadenitis (NHL)is an idiopathic reason of lymphadenopathy which rather affects the young population. In this article, 3 cases which have applied to our Internal Medicine Policlinic with painful lymphadenopathy within four months and which were diagnosed with NHL have been presented and their clinical features discussed.